In Vivo (23)Na Nuclear Magnetic Resonance Study of Maintenance of a Sodium Gradient in the Ruminal Bacterium Fibrobacter succinogenes S85 - Schwaab, Véronique (American Society for Microbiology, 2001)
Sodium gradients (ΔpNa) were measured in resting cells of Fibrobacter succinogenes by in vivo (23)Na nuclear magnetic resonance using Tm(DOTP)(5−) [thulium(III) 1,4,7,10-tetraazacyclododecane-N′,N′′,N′′′-tetramethylenephosphonate] as the shift reagent. This bacterium was able to maintain a ΔpNa of −55 to −40 mV for extracellular sodium concentrations ranging from 30 to 200 mM. Depletion of Na(+) ions during the washing steps led to irreversible damage (modification of glucose metabolism and inability to maintain a sodium gradient).